International Legal Perspective on the Implementation of the Death Penalty Case Study of Mary Jane Fiesta Veloso (Universitas Negeri Semarang, 2020)
Mary Jane, a citizen from the Philippines, was arrested on April 25, 2010 by the police at Adi Sutjipto Airport, Yogyakarta, for her efforts to smuggle 2.6 kilograms of Heroin. In this case, finally in October Marry Jane was sentenced to death by the Sleman District Court on charges of violating Article 114 paragraph 2 of Law Number 35 Year 2009 Regarding Narcotics. Mary Jane sent clemency, which was rejected by President Jokowi. Mary Jane then tried to submit the Judicial Review (PK) and the PK session where the Sleman District Court decided to forward the Mary PK to the Supreme Court (MA). From this there are the main issues raised in this paper namely how international legal review responds to the death penalty that still occurs in several countries, especially Indonesia in Narcotics crime cases and what is the legal basis for the death sentence for drug dealers. The purpose of writing this paper is to increase knowledge of the legality of the death penalty in terms of human rights and international law. This writing uses a research method conducted by studying and analyzing legal materials and related legal issues. Through international legal instruments as in Article 3 of the Universal Declaration of Human Rights (UDHR), Article 6 paragraph (1) of the International Covenant on Civil and Political Rights (ICCPR) and in the Second Optional Protocol to the International Covenant on Civil and Political Rights which are protocols additional to the ICCPR which obliges participating countries to ban the implementation of the death penalty and abolish the death penalty. However, the results of the study show that the application of the death penalty for Narcotics crimes must be carried out to protect the public by capital punishment for Narcotics offenders which does not conflict with human rights and international conventions of civil and political rights so that the death penalty can be applied in Indonesia.